IN VITRO EVALUATION OF PHYTOCHEMICAL COMPOUND FOR ANTIBACTERIAL ACTIVITY AT MURRAYA KOENIGII LEAF EXTRACT AGAINST THE GROWTH OF ESCHERICHIA COLI - Elbert, Elbert; Adella, Cut Adeya; Faradina, Dwi; Lubis, Lokot Donna; Khosasi, Felix (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2024)
Introduction: In developing nations, like Indonesia, urinary tract infection, or UTI, is a frequent infection in women that results from the growth of microorganisms in the urinary tract. Escherichia coli is the most common cause. Antibiotics are the major form of treatment; however, misuse of these drugs has led to resistance. Innovation in potential medical plants is crucial. The curry leaf plant (Murraya koenigii) is one of them. Methods: The agar diffusion method was used to assess antibacterial activity. Murraya koenigii leaves were gathered from a garden in Tanjong Morawa. Escherichia coli ATCC 25922 is the type of bacteria that is used. Using 96% ethanol as the solvent, Murraya koenigii leaves were extracted using the maceration method. There were six treatments with concentrations of 6.25%, 12.5%, 25%, and 50%, positive control levofloxacin, and negative control DMSO. Results: The results of the phytochemical screening of the extracts showed that metabolites like flavonoids, tannins, and triterpenes had antibacterial effects. Data on the diameter of the inhibition zone were examined using the Kruskal-Wallis statistical test. The findings demonstrated that all treatments had statistically significant differences (p<0.05). Discussions: The presence of compounds such as flavonoids, tannins, and triterpenes in curry leaf extract has an antibacterial effect on Escherichia coli. This compound can prevent the creation of nucleic acids, inhibit cell membrane function, damage the permeability of bacterial cells, and deactivate bacterial enzymes. Conclusion: The ethanol extract of curry leaves has an inhibitory effect on the growth of Escherichia coli bacteria.